Intelligent Exchanges and Coordination in Multimodal Supply Chains - René Föhring; Stephan Zelewski (Operational Excellence in Logistics and Supply Chains: Optimization Methods, Data-driven Approaches and Security Insights. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 22, 2015)
The prototype ORFE of an Online Rail Freight Exchange was developed as part of the CODE24 project. It demonstrates functionalities for a more transparent communication of available transport services and also supports the configuration of multimodal supply chains. The paper describes the efforts and research outcomes of the implementation of ORFE as well as problems that emerged after its finalization. These problems led the authors of this paper to the draft of a new market place concept: Agent-based Freight Exchanges (AFEX). These yet to be implemented, highly automated and interconnected market places are designed to provide autonomous software agents with the infrastructure to perform contractually binding auctions of multimodal freight transport services utilizing a combinatorial exchange model while addressing problems commonly associated with existing market places.
10419/209191; https://econpapers.repec.org/RePEc:zbw:hiclpr:22
Keywords: 650; Intermodal Transports; Logistics Modelling; Multi-Agent Systems; Combinatorial Auctions